Retail competition and shelf space allocation - Sant'Anna, Marcelo Castello Branco (2010)
We develop a model to study shelf space allocation in retail. Retailers compete for consumers not only choosing prices but also by the space allocated to each product on shelves. Our approach depart from the existing literature on shelf allocation, as we model the problem of price setting and shelf allocation in an oligopolistic retail market. We present a simple model of retail competition in which prices are dispersed in the crosssection of stores but shelf allocation is not.